OPTIMALISASI USAHA KESEHATAN SEKOLAH/MADRASAH (UKS/M) SEBAGAI DAYA UNGKIT MUTU SUMBER DAYA MANUSIA - Siti Ngaisah Nurochim; Nurochim Nurochim (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2020)
Humans are the capital of national life. Human resources that can uphold a nation are quality human resources. Quality human resources are human resources that have positive skills, knowledge, and psychological qualities. To achieve quality human resources obtained through education. It is very important to describe how schools can form quality human resources, one of which is through the school health program. The method used in this article is a literature review, starting with analyzing written sources from social media and scientific article manuscripts. These sources analyze the quality of human resources, school health program business policies, and the quality of human resources caused by human resource programs. Quality human resources are people who have the skills, knowledge of religious knowledge, have a good character. Quality human resources, obtained from schools, especially school health programs. Through school health program, accustomed to developed an optimal physical and mental health. Optimal health, is the initial capital to carry out various education and play a professional role in life.